Facile assembly of Bi2O3/Bi2S3/MoS2n-p heterojunction with layered n-Bi2O3 and p-MoS2 for enhanced photocatalytic water oxidation and pollutant degradation - Ke, Jun; Liu, Jie; Sun, Hongqi; Zhang, H.; Duan, Xiaoguang; Liang, P.; Li, Xin Yong; Tade, Moses; Liu, Shaomin; Wang, Shaobin (Elsevier BV, 2017)
© 2016 Elsevier B.V. As an important half reaction in solar-driven water splitting, it is still a challenging issue to develop low-cost and high efficient photocatalysts for water oxidation process. In this study, we reported a facile strategy for controllable synthesis of three-component Bi2O3/Bi2S3/MoS2 n-p heterojunction based on the formation of the intermediate Bi2S3 by coupling Bi2O3 and MoS2. The Bi2S3 was easily formed due to the strong interaction between Bi3+ and S2- ions with the assistance of the hydrothermal treatment. As a result, the prepared Bi2O3/Bi2S3/MoS2 nanocomposite exhibits enhanced ability of photocatalytic water oxidation (529.1 µmol h-1 g-1cat), which is 1.5 and 12.5 times higher than that of pure Bi2O3 and MoS2, respectively, under simulated solar light irradiation. Furthermore, the photoelectrochemical results reveal that the charge transportation feature and the donor density were apparently enhanced after the introduction of highly conductive layered MoS2, which indicates the enhancement of the photo-response and the improvement of charge separation efficiency.